Suicide and the economy: A regional analysis of Italy - Roberto Cellini (Journal of Applied Economics, 2023)
This note investigates the empirical pattern of suicides across Italy over the last 15 years. Typically, a country shares similar basic cultural and social macro-features. Yet in Italy there are marked variations across the regions such that it provides a useful setting to examine the economic factors that influence suicidality. The results align with some earlier work positing an N-shaped Kuznets curve linking income and the suicide rate. Female participation in the labour market emerges as a robust explanatory factor for male and female suicide rates.
Keywords: 330; gender; Income; labour market participation; Suicide